Microsoft Excel Training to Improve High School Students' Skills in Data Analysis at Sutomo 2 School, Medan - Pasaribu, Sutrisno Arianto; Marpaung, Preddy; Jannah, Miftahul; Halawa, Dedi Dermawan; Banuari, Nidya; Ananda, Shela (Jurnal Pengabdian Pancasila (JPP), 2024)
Microsoft Excel training for high school students at Sutomo 2 Medan High School aims to improve data analysis skills and digital literacy. In the growing digital era, the ability to use data processing software such as Excel has become very important. The program is designed to equip students with basic to intermediate skills, including the use of formulas, charting, and data analysis using Pivot Table. Through this training, students are expected to prepare themselves for the challenges of the world of work and further studies. In addition, this activity also benefits the school and community by supporting the development of information technology-based education. The results of the training showed a significant improvement in students' skills, which contributed to the quality of education and social welfare in the neighborhood.